Friction Behaviour of Multilayered Graphene against Steel. (2016) - Banerji, A.; Bhowmick, S.; Lukitsch, M.J.; Alpas, A.T.
ABSTRACT: Frictional behaviour of multilayered graphene was studied in air with different relative humidity (RH) levels (10–52% RH). Pin-on-disk type sliding tests were performed and the running-in and steady state coefficient of friction (COF) values were measured against M2 tool steel counterface. On increasing the RH, multilayered graphene showed a reduction in steady state COF from 0.11 at 10% RH to 0.08 at 52% RH. The low steady state COF values observed in graphene could be attributed to the transfer layer formed on the M2 tool steel counterface. A sliding-induced structural change was observed in graphene transfer layers which could have facilitated the graphitic transfer layer formation. The multilayered graphene showed a lower steady state COF values at all RH compared to non-hydrogenated diamond-like carbon (NH-DLC) which recorded a steady state COF of 0.47 at 10% RH and 0.25 at 52% RH.